Chirality distribution and transition energies of carbon nanotubes - Maultzsch, Janina; et al. (Physical Review Letters, 2004)
From resonant Raman scattering on isolated nanotubes we obtained the optical transition energies, the radial breathing mode frequency, and the Raman intensity of both metallic and semiconducting tubes. We unambiguously assigned the chiral index (n(1),n(2)) of approximate to50 nanotubes based solely on a third-neighbor tight-binding Kataura plot and find omega(RBM)=(214.4+/-2) cm(-1) nm/d+(18.7+/-2) cm(-1). In contrast to luminescence experiments we observe all chiralities including zigzag tubes. The Raman intensities have a systematic chiral-angle dependence confirming recent ab initio calculations.